Komunikasi Efektif Dalam Pembelajaran Daring Selama Masa Pandemi Covid 19 - Novita Maulidya Jalal; Nadia Islami Nur Fadilla; Ismalandari Ismail; Rahmawati Syam; Wilda Ansar (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The Covid-19 pandemic has caused various impacts, one of which is the transformation of the learning system in Indonesia that applies online learning. The online learning method causes communication that occurs between educators and students not face-to-face, but through online applications. The purpose of this study was to determine the description of effective communication during the online learning period during the covid 19 pandemic. The research method used was a library research method or literature review. The subjects in this study were 10 articles related to effective communication during online learning during the covid 19 pandemic. The instrument used was a secondary data source in the form of scientific journal articles. The data analysis used is descriptive qualitative by drawing conclusions from the data obtained from previous studies. The results of this study indicate that communication will run effectively if there are the following efforts: (1) providing task assistance through the whatsapp application, (2) using problem solving methods in carrying out tasks so that two-way communication is established, (3) holding meetings through the application Zoom, Google Meetings, WhatsApp for a more detailed explanation of the material, (4) delivering complete, concrete, and simple messages or information, using language and ethics in communicating, and considering time in communicating to be effective and efficient, (5) using models synchronous and asynchronous communication, (6) conducive internet network conditions, (7) learning media and delivery of interesting material.